Shaping the entrepreneurial university: Two experiments and a proposal for innovation in higher education - Etzkowitz, H.; Dzisah, J.; Clouser, M. (SAGE, 2021)
The paper delineates three elements of an entrepreneurial university in practice through innovations demonstrating the academic entrepreneurial transition: the Novum Trivium, Professors of Practice (PoPs) and Link initiatives. The Novum Trivium provides a model for the integration of entrepreneurship into a liberal arts curriculum, so that students learn how to put their knowledge to use and acquire a new language and new cultural understanding to interact globally. The PoPs initiative interlinks firm and university through shared dual roles in each setting, attracting back to the university on half time basis scientific entrepreneurs from industry to serve as entrepreneurial role models. The Link projects build on ties between a leading entrepreneurial university (Stanford) and an aspiring one (Edinburgh), taking advantage of the fact that each university is already embedded in its region and could be linked to the other’s entrepreneurial culture. The paper demonstrates how industry and higher education are integrated by these initiatives, with the elements of each embedded in the other through shared resources, people and practices.
Research Article
Keywords: Entrepreneurial education; entrepreneurial university; entrepreneurial university linkages; Novum Trivium; Professors of Practice